Utilizing Local Economic Development As a Technique for Development to Combat Poverty and Unemployment: A Case Study of Polokwane Municipality, South Africa - Jonas MAKGOBA; Ernest MLAMBO (International Journal of Environmental, Sustainability, and Social Science, 2024)
For many countries throughout the world, unemployment, poverty, and inequality are the biggest problems. These also apply to South Africa. In essence, local economic development (LED) is an ongoing procedure that is spearheaded by local stakeholders, particularly the local government, and built upon local efforts to stimulate the local economy and provide employment in a given area. Using the Polokwane municipality as a case study, the study aims to examine the contribution of local economic development in the reduction of unemployment in South Africa. The research also aims to ascertain how much Polokwane Municipality's local economic development organizations aid to the reduction of poverty. To obtain a thorough understanding of the subject matter, the study will employ a qualitative research approach and involve participants from various municipal levels who are involved in local economic development, such as agencies, municipal officials, and beneficiaries. The study followed a qualitative research methodology, which is a type of social science research that collects and works with non-numerical data and that seeks to interpret meaning from these data that help us understand social life through the study of targeted populations or places, and it employed theme analysis to find, arrange, and present themes and their sub-themes surfaced from study interviews. The research produced suggestions for using local economic development to reduce poverty and provide jobs.